Rainwater storage tank sizing: Case study of a commercial building - Cristina Santos (2014)
To revert the non-sustainable tendency of increasing surface and groundwater extraction to satisfy the rising demand of water, a moresustainable use of this essential resource must be done. Rainwater harvesting (RWH) systems are progressively becoming a part of thesustainable water management measures. However, they require a careful study to assess their feasibility, especially in large buildings,since they employ considerable investment costs and, in some cases, long payback periods.This paper aims to define the best configuration for an RWH system of a commercial building, considering different scenarios of suppliednon-potable uses, each of them with a subsequent rainwater storage volume. The results from three different scenarios arepresented.